Analisis Dan Perancangan Aplikasi E-Learning Berbasis Web (Study Kasus SMP Negeri 16 Kota Jambi) - Pratama, Anggi Andika; Assegaff, Setiawan (LPPM Universitas Dinamika Bangsa, 2021)
E-Learning is a edication system that uses electronic applications that support the development of teching and learing activities with internet media or other computer network media. SMO Negeri 16 the teaching process is still done sirectly through the face. With the existence of e-learning the teaching and learning process becomes simple. The method user is a method of data collection, namerly observation, intervies of quasting and answer directly of trusted sources. The design is done by making unifield modeling language. The program is created achieved in making e-learning is to facilitate the learning process without being bound by time and place. With this e-learaning teacher cab upload subjeck matter and upload of dowload assgnments an any time and provide student grades. The conclusion wiht the existence of e-learning is to facilitate learning bettwen teachers and students